ACUTE MESENTERIC VENOSUS THROMBOSIS IN A PREGNANT WOMAN - Eftimova, Aleksandra; Kocevska, Ana; Pushevska, Anamarija Shpisikj; Chelebieva, Jasmina (Journal of Morphological Sciences; Vol 6 No 3 (2023): JMS, 2023)
Mesentric venous thrombosis is a blood clot in one or more of the main veins that squeeze blood from the intestine. Superior mesenterine vein is most commonly involved in the process.  The appearance of MVT is usually rare.  The aim of this study is to identify the incidence and obstetric risk factors. This study will analyse a pregnant woman who appeared with an MVT in the 30 th  gestational week. A 33-year-old primigravid woman was admitted to the Special Hospital for Gynecology and Obstetrics "Mother Teresa" in Cair, Skopje during the 35 th week of pregnancy. The second day after admission, she complained of more intense abdominal pain, anorexia, vomiting and abdominal dystency that were disproportionate to physical signs.  The entire ileum, part of the yeunum and part of the ascendant colon were gangrenose, and thromboembolism was discovered in the corresponding mesenteric veins. Histopathological analysis also revealed extensive edema, hemorrhagic, inflammatory infiltration and necrosis in the resected intestine and widespread thrombosis in mesenteric venous lumens. Although MVT diagnosis during pregnancy is difficult due to its small incidence and uncharacteristic symptoms, signs and laboratory results, MVT is often the main cause of severe abdominal pain during pregnancy and should be included in the differential diagnosis of pregnant women with acute abdominal pain. Key words: mesentric venous thrombosis, abdominal pain, pregnancy